Transparency in IPO mechanism : information production, IPO pricing and investors' participation - Neupane, Suman (Cranfield University, 2011)
In this doctoral thesis we bring together some empirical analysis on investors’ participation in initial public offering (IPOs) from a market whose characteristics are unique and significantly different from US and other important IPO markets. There are two important features which distinguishes the Indian IPO market. First, the Indian IPO market is characterised by a high level of transparency. Information on the participation of different investor categories is publicly available during the offer period on a real time basis. Second, Indian IPO firms are also required to reserve and allocate pre-determined fraction of total shares on offer to different investor categories participating in the IPO. Our first empirical study shows that the transparency in the mechanism creates highly inelastic demand curves for a large number of IPOs. Analysis of demand over-time shows that while institutional investors take the lead in subscribing to strong IPOs, noninstitutional investors do so in weak IPOs, but perhaps not always with an honest intent. Our analysis of IPO pricing shows that favourable demand by uninformed investors is positively associated with a high IPO price. Further, while reputed underwriters appear to exercise far more caution and restraint in setting prices, we find that in a large number of IPOs, less reputed underwriters ignore information produced during the offer period and set the price at the upper bound of the price range. Our findings suggest that the transparency in allocation mechanism appears to be a double edged sword for the uninformed (retail) investors. We recommend a change in the current regulation to protect investor’s welfare. We also examine the influence of the participation of different investor categories on initial returns. Unsurprisingly, we find that while the participation of both the informed investor categories significantly influences initial returns, the participation of retail investor losses its significance in explaining initial returns for bookbuilding and auction IPOs. We also analyse the participation of informed institutional investors to examine whether the presence of new bank loans at the time of the IPO reduces information asymmetry. Our results show that presence of bank loans do not appear to reduce information asymmetry as institutional investors participate significantly less in IPOs with new bank loans. While this result is contrary to prior studies on bank loan announcements, it is consistent with a recent study which shows that prior studies on bank loan announcements are plagued by sample selection issues. In our final empirical analysis we examine the participation of employees in IPOs and analyse whether such participation can predict superior financial and operating performance of the firm. We find that IPOs with high employee participation offer significantly higher initial returns than IPOs with low employee participation. We also find that firms with high employee participation in their IPOs exhibit superior post IPO operating performance. Further, we find that the prior participation of other investor categories, in particular the institutional investors, does not appear to influence the participation of employees in IPOs. Our results suggest that employees have valuable private information about the quality of the firm. The evidence presented in the study suggests that in the context of Indian IPOs, where data on investors’ participation is available on a real time basis, uninformed investors may use information on employee participation to select well performing IPOs.